EMPIRICAL ANALYSIS OF LIVESTOCK PRODUCTIVITY THROUGH IMPROVED BREEDING IN PUNJAB, PAKISTAN - M. Ashfaq; R. Kousar; M. S. A. Makhdum; J. Nasir (Journal of Animal and Plant Sciences, 2020)
In Pakistan, the productivity of the livestock sector is lower than its capacity due to lack of breeds with high productive potential, nutrition deficiency and poor disease control facilities. This study explores the potential of the livestock sector to move towards more productive breeds of cattle. Primary data were collected from 340 livestock farmers of Punjab Province through stratified random sampling technique. Endogenous Switching Regression (ESR) is employed to identify factors influencing the farmer’s decision to adopt superior/exotic breeds of buffaloes and cows and impact of adoption on the gross margins. The results of adoption equation reveal that farmer’s decision to adopt exotic breed depends positively on the proximity of his house to livestock market, years of schooling, operational land, access to hired labour and contact with extension agents. Results also show that different socio-economic factors have differential impact on the gross margins of both adopters and non-adopters. There is need of policy reforms to eliminate the constraints of shifting towards high productive breeds.
Keywords: Improved Livestock Breed; Constraints and Impact Analysis; Endogenous Switching Regression (ESR); Punjab-Pakistan